THE USE OF TRANSLATION TECHNIQUES IN TRANSLATING CULTURAL WORDS IN THE DA VINCI CODE NOVEL FROM ENGLISH INTO BAHASA INDONESIA - Deny Kuswahono (Anaphora : Journal of Language, Literary, and Cultural Studies, 2020)
The purpose of this study is to identify techniques of translation that are applied in translating cultural words in The Da Vinci Code novel from English into Bahasa Indonesia and interpreting the reason of the translator in applying those techniques. This study uses descriptive and qualitative approach. The cultural words found in the novel were collected in tables and categorized based on five types of culture that are proposed by Newmark. Result of the study shows that there are 171 cultural terms and there are six Molina and Albir’s techniques of translation applied by the translator, those are transposition with 23 occurrences, pure borrowing with 118 occurrences, naturalized borrowing with 10 occurrences, calque with seven occurrences, established equivalence with four occurrences, and discursive creation with nine occurrences. Pure borowing is the technique applied most by the translator. This was done by the translator in order that information conveyed by the author of the original novel could be accepted by the target readers accurately.